2017
DOI: 10.1016/j.jss.2017.05.027
|View full text |Cite
|
Sign up to set email alerts
|

Thrombelastography indicates limitations of animal models of trauma-induced coagulopathy

Abstract: Introduction Thrombelastography (TEG) has been used to characterize the coagulation changes associated with injury and shock. Animal models developed to investigate trauma-induced coagulopathy (TIC) have failed to produce excessive bleeding. We hypothesize that a native TEG will demonstrate marked differences in humans compared to these experimental models, which explains the difficulties in reproducing a clinically relevant coagulopathy in animal models. Methods Whole blood was collected from 138 healthy hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 19 publications
1
14
0
Order By: Relevance
“…The addition of tissue factor to TEG or EXTEM has been thought to reduce the sensitivity of both tests by masking coagulation abnormalities. 32,33 For this reason, the use of native assays (without activators), for example, remains relevant for use in research owing to its ability to dampen false signals to determine fibrinolysis and therefore the cutoff points, which predict transfusion needs in TIC. 32 However, a recent comparison of native citrated kaolin, and rapid TEG suggested that transfusion thresholds can be used with confidence without concern for masking coagulation abnormalities by using an activated TEG, as there was significant overlap in the performance of the these three TEG assays.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of tissue factor to TEG or EXTEM has been thought to reduce the sensitivity of both tests by masking coagulation abnormalities. 32,33 For this reason, the use of native assays (without activators), for example, remains relevant for use in research owing to its ability to dampen false signals to determine fibrinolysis and therefore the cutoff points, which predict transfusion needs in TIC. 32 However, a recent comparison of native citrated kaolin, and rapid TEG suggested that transfusion thresholds can be used with confidence without concern for masking coagulation abnormalities by using an activated TEG, as there was significant overlap in the performance of the these three TEG assays.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these values provide insight into the activity of coagulation factors in the blood sample. Heparin was used as an anticoagulant because rats are more prone to coagulation at baseline and we were unable to determine treatment effect without anticoagulation of the sample, as clotting occurred too rapidly . Citrate was not used as an anticoagulant as studies looking at TF-dependent reactions are impaired by citrate chelation .…”
Section: Resultsmentioning
confidence: 99%
“…Heparin was used as an anticoagulant because rats are more prone to coagulation at baseline and we were unable to determine treatment effect without anticoagulation of the sample, as clotting occurred too rapidly. 28 Citrate was not used as an anticoagulant as studies looking at TF-dependent reactions are impaired by citrate chelation. 29 Furthermore, the high levels of calcium required to overcome citrate chelation can negatively affect nanofiber formation.…”
Section: Resultsmentioning
confidence: 99%
“…It is a known phenomenon that swine are hypercoagulable at baseline. 18 This hypercoagulable state has been shown to be augmented through the act of instrumentation. 19 Thus, instrumentation alone may have induced the coagulopathy seen in the control animals.…”
Section: Discussionmentioning
confidence: 99%